Sosialisasi Mengenai Dampak Game Online Terhadap Minat Belajar Siswa SDN 06 Tanjung Batu - Amaliyah, Rizki; Juni (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2025)
Universities have an important role in implementing the Tri Dharma of Higher Education, one of which is through community service which is realized in the form of Thematic Real Work Lectures (KKNT). Bina Darma University Palembang organizes the KKNT program with the aim of improving the quality of human resources and developing the potential of certain regions. In this activity, one of the programs carried out was socialization regarding the impact of online games on students' interest in learning at SD Negeri 06 Tanjung Batu. Online games have become part of children's lifestyle and can have both positive and negative impacts. This socialization aims to increase students' and teachers' understanding of the impact of online games as well as strategies for managing playing time so that it does not interfere with the learning process. The results of this activity show that continuous education and collaboration between students, teachers and parents are very necessary to reduce the negative impact of online game addiction on students' interest in learning.